A Class of Algorithms for Zeros of Polynomials - Uwamusi, Stephen Ehidiamhen (Biological Sciences - PJSIR, 2005)
A class of polytype algorithms for the determination of zeros of polynomial equation of single variable was constructed from Jarratt’s asymptotic error constant using the well-known Chevbyshev’s comparison series. The method was synthesized from the Taylor series iterative method. The climax of the findings was that the proposed formula can effectively model the determination of zeros of polynomial equations of the type often encountered in the Givens orthogonal matrix transformation process